Transdisciplinarity and co-creation applied to the social learning process: a case study within the scope of the Demola methodology - Valduga, Tatiane; Balão, Ana (Aprender, 2023)
This article aims to present, discuss and analyze the importance in learning processes of collective construction for building a higher education institution open to the community and concerned with contributing to the development of a collaborative and sustainable society. For this purpose, co-creation, through transdisciplinary perspectives, applied to a challenge in the context of tourism, proves to be a key tool in the learning processes focused on the needs of the community. In these co-creation and collaboration approaches, different actors and knowledge are valued in the construction and dissemination of new knowledge. It is concluded that this model can enhance new learning contexts and boost a learning culture focused on community responsibility. Stimulating co-creation can find in higher education a strong ally for building a more collaborative society, and therefore more sustainable. The study is part of the project called "Link me Up: 1000 Ideas - Support System for Co-creation of Innovation, Creativity and Entrepreneurship", developed by the Polytechnic Institute of Portalegre among other educational institutions, with financial support from the European Union.
Keywords: logical framework; higher education; training; transdisciplinarity